Semiotic Analysis of Local Cultural Representation and Fingerprint Painting Authenticity on Indonesiana TV's YouTube Channel - Ananda Salsa Sabila; Sara Dwi Anjani; Somadi Sosrohadi (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study explores the concept of representation, semiotics, and visual communication through the lens of fingerprint painting as a unique form of abstract art. Drawing on theories from Stuart Hall, John Fiske, Ferdinand de Saussure, Roland Barthes, and Charles Sanders Peirce, the research examines how meaning is constructed through signs, symbols, and artistic expression. Representation is understood as a process of encoding and decoding meaning, where language and media shape social perceptions. Semiotics, as introduced by Saussure and expanded by Barthes and Peirce, provides a framework for analyzing how signs function in communication and artistic expression. Fingerprint painting is investigated as a visual language that conveys identity, tradition, and cultural symbolism. This research applies Peirce’s semiotic theory to analyze fingerprint painting as a system of signs, incorporating icons, indices, and symbols. The study employs a qualitative descriptive method, focusing on audiovisual data from the documentary Di Balik Lukisan Sidik Jari, supported by literature reviews and media analysis. Data collection techniques include observation, listening, and note-taking to interpret verbal and nonverbal elements within the documentary. Findings indicate that fingerprint painting serves as more than an aesthetic medium; it is a symbolic representation of cultural identity, tradition, and personal expression. Through semiotic analysis, the research highlights how fingerprints, as unique individual markers, contribute to the authenticity of artistic creation. This study provides insight into the role of representation in art and the broader implications of semiotic analysis in visual culture.